A hybrid algorithm for image watermarking against signal processing attacks - Singh A.K.; Dave M.; Mohan A. (My University, 2025)
In this paper, we have presented a hybrid image watermarking technique and developed an algorithm based on the three most popular trans form techniques which are discrete wavelet transforms (DWT), discrete cosine transforms (DCT), and singular value decomposition (SVD) against signal processing attacks. However, the experimental results demonstrate that this algorithm combines the advantages and remove the disadvantages of these three transform. This proposed hybrid algorithm provides better imperceptibility and robustness against various attacks such as Gaussian noise, salt and pepper noise, motion blur, speckle noise, and Poisson noise etc. © 2013 Springer-Verlag.